(untitled) (Materiali di Estetica. Terza serie, 2022)
Nicola Vitale walks a side path to the smooth march of technocratic rationalism. A rationalism dried up in the imagination, in the capacity for vision, in the sense of community belonging that makes us human beings, as Aristotle taught. Snow White, from a Disney fairy tale, returns to its symbolic powerful significance of alchemical narration where everything, even the most divisive evil, finds meaning and place.